2013
DOI: 10.1212/wnl.0b013e318292a2d2
|View full text |Cite
|
Sign up to set email alerts
|

The midbrain to pons ratio

Abstract: Objectives: MRI-based measurements used to diagnose progressive supranuclear palsy (PSP) typically lack pathologic verification and are not easy to use routinely. We aimed to develop in histologically proven disease a simple measure of the midbrain and pons on sagittal MRI to identify PSP.Methods: Measurements of the midbrain and pontine base on midsagittal T1-weighted MRI were performed in confirmed PSP (n 5 12), Parkinson disease (n 5 2), and multiple system atrophy (MSA) (n 5 7), and in controls (n 5 8). Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
147
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(154 citation statements)
references
References 22 publications
5
147
1
1
Order By: Relevance
“…The similarity of ROI-measured atrophy rates between PSP and PSP-DAV supports the conclusion that the larger PSP-DAV sample size enabled detection of smaller cortical changes using VBM maps, which indicate statistical significance but not magnitude. In addition, the midbrain to pons ratio, which has previously been shown to be decreased in PSP, [26][27][28][29][30] was nearly identical in the PSP and PSP-DAV groups and smaller than in the CBS or NC group. Future studies of autopsy-confirmed CBD and PSP cases will be necessary to definitively determine the differences in rates of volume loss between these disorders.…”
Section: Magnitude Of Longitudinal Volumetric Changes In Definedmentioning
confidence: 56%
See 1 more Smart Citation
“…The similarity of ROI-measured atrophy rates between PSP and PSP-DAV supports the conclusion that the larger PSP-DAV sample size enabled detection of smaller cortical changes using VBM maps, which indicate statistical significance but not magnitude. In addition, the midbrain to pons ratio, which has previously been shown to be decreased in PSP, [26][27][28][29][30] was nearly identical in the PSP and PSP-DAV groups and smaller than in the CBS or NC group. Future studies of autopsy-confirmed CBD and PSP cases will be necessary to definitively determine the differences in rates of volume loss between these disorders.…”
Section: Magnitude Of Longitudinal Volumetric Changes In Definedmentioning
confidence: 56%
“…[26][27][28][29][30] At all time points, both PSP and PSP-DAV groups had lower midbrain to pons ratios than NC and CBS groups (figure e-2). Moreover, midbrain/pons ratios within all groups remained stable over 1 year in all groups.…”
Section: Magnitude Of Longitudinal Volumetric Changes In Definedmentioning
confidence: 96%
“…The placement of ROI was determined by a previous report (13). Elliptical ROI were placed over the pons in the midsagittal slice (Fig.…”
Section: Csf Flow Imagingmentioning
confidence: 99%
“…In all cases, the posterior border of the pontine base was clearly identified and did not include the pontine tegmentum. All measurements were performed by another rater who was blinded to the clinical information (13).…”
Section: Csf Flow Imagingmentioning
confidence: 99%
“…It is reflected in the hummingbird sign, which appears to show some specificity for PSP (1,2), although negative results have also been reported (3). Midbrain atrophy can also be observed in vascular parkinsonism (4), primary progressive apraxia of speech (5), and dementia with Lewy bodies (6).…”
Section: Introductionmentioning
confidence: 99%